1977
DOI: 10.1128/aem.34.4.342-346.1977
|View full text |Cite
|
Sign up to set email alerts
|

Production of uricase by Candida tropicalis using n-alkane as a substrate

Abstract: Production of uricase (urate oxidase, EC 1.7.3.3) by n-alkane-utilizing Candida tropicalis pK233 was studied. Although the yeast showed very low enzyme productivity under growing conditions on glucose or an n-alkane mixture (C,O to C13) (<2 U/g of dry cells), enzyme formation was enhanced markedly in an induction medium consisting of potassium phosphate buffer, MgSO4, uric acid, and an n-alkane mixture (47 U/g of dry cells) or glucose (21 U/g of dry cells). Of the carbon sources tested, the n-alkane mixture wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Most vertebrates possess uricase, except humans and higher apes, which became not functional by point mutation during evolution resulting in the formation of a redundant protein [25] . Uricase is localized inside microorganisms, especially Bacillus pasteurii [26] , Proteus mirabilis [27] , and Escherichia coli [28] , while other microorganisms could produce them extracellularly by changing certain components of the culture media as in Streptomyces albosriseolus [29] , Microbacterium [30] , Bacillus thermocatenulatus [31] , Candida tropicalis [32] , and Pseudomonas aeruginosa [33] .…”
Section: Enzymatic Degradation Of Uric Acid By Microorganismsmentioning
confidence: 99%
“…Most vertebrates possess uricase, except humans and higher apes, which became not functional by point mutation during evolution resulting in the formation of a redundant protein [25] . Uricase is localized inside microorganisms, especially Bacillus pasteurii [26] , Proteus mirabilis [27] , and Escherichia coli [28] , while other microorganisms could produce them extracellularly by changing certain components of the culture media as in Streptomyces albosriseolus [29] , Microbacterium [30] , Bacillus thermocatenulatus [31] , Candida tropicalis [32] , and Pseudomonas aeruginosa [33] .…”
Section: Enzymatic Degradation Of Uric Acid By Microorganismsmentioning
confidence: 99%
“…These days many fungal sources have been used for uricase production such as Candida tropicalis [11], Aspergillus flavus [36], and Candida utilis [37]. In this study, 40 soil samples were collected and microorganisms with uricase production ability were isolated for studying optimized conditions for increasing uricase production.…”
Section: Discussionmentioning
confidence: 99%
“…Microorganisms such as bacteria and fungi normally have uricase enzymes [7], so they are used for uricase production. Some of the microorganisms used to produce uricase are Streptomyces exfoliatus [9], Pseudomonas aeruginosa [7], Bacillus subtilis [10], Candida tropicalis [11], and Aspergillus flavus [8]. Wheat, chickpea, and broad bean are plant sources, which were studied for uricase production and isolation [5].…”
Section: Introductionmentioning
confidence: 99%
“…A thermostable uricase was obtained from Microbacterium (7) and Bacillus thermocatenulatus (8). Tanaka et al (9) demonstrated that in addition to uric acid, xanthine, guanine, adenine, and hypoxanthine were also effective for inducing uricase in Candida tropicalis. Abdel-Fattah et al (10) found that glucose, the medium used, pH, CuSO 4 , and FeSO 4 all had a highly significant effect on the uricase activity produced by Pseudomonas aeruginosa, based on statistical experimental designs.…”
Section: Introductionmentioning
confidence: 99%